Efficiency of Arthrocentesis with Hyaluronic Acid in TMJ Disc Derangement - Hurraia Zahid, Nouman Rauf, Ameer Muhammad Farooq Siddiqi, Fariha Farooq, Rabiya Imdad, Arham Chaudhry, Zahid Sarfaraz Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of this research was to determine if arthrocentesis for Temporomandibular Joint (TMJ) issues, with or without hyaluronic acid, is an effective treatment. Study Design: A Prospective study Place and Duration: This study was carried out at the Sardar Begum Dental College from January 2022 to June, 2022. Methods: This research included 40 individuals of both sexes with TMJ disc problems. After informed written consent, patients' age, sex, side, and effusion type were examined. Evenly separate patients into two groups. Group I got arthrocentesis in 20 cases and group II got hyaluronic acid in 20 cases. Standard two-needle arthrocentesis was used. Maximum mouth opening, pain reduction, and complications were compared between both groups. Data was analyzed using SPSS 18.0. Results: Pre-treatment, MMO in group I was 29.7±11.37 mm while in group II maximum mouth opening was 30.4±11.61 mm. Post treatment, we found that in group I MMO was 43.9±7.43 mm and in group II 45.6±23.62 mm but did not found any significantly difference after 1.5 years of follow up 40.6±16.28 in group I and 42.7±4.17 mm in group II. Using VAS, pain scores were reduced 1.3±6.87in group I and 0.5±2.3 in group II, with p value 0.001 after treatment. Conclusion: In this research, we found that arthrocentesis was a successful and safe approach for treating disc derangement in the temporomandibular joint (as measured by an increase in MMO and a decrease in pain score), with arthrocentesis utilizing hyaluronic acid showing marginally improved outcomes. Keywords: Arthrocentesis, Pain score, Temporomandibular Joint disc, MMO